Method of simultaneous determination of carbamazepine and carbamazepine-10,11-epoxide by HPLC-MS/MS - T. A. Rodina; E. S. Melnikov; A. V. Sokolov; A. B. Prokofiev; V. V. Arkhipov; G. V. Adamov; D. L. Pozdnyakov; Yu. V. Olefir (Регуляторные исследования и экспертиза лекарственных средств, 2018)
Carbamazepine is the drug of first choice in the treatment of trigeminal neuralgia, epilepsy and other neurological diseases. Carbamazepine is known to have a narrow therapeutic range, and hereby the auto-induction of its metabolism with prolonged use cause the reduction of its therapeutic efficacy. Phenotyping of patients by the rate of carbamazepine metabolism allows to perform individual drug dose adjustment and to avoid the occurrence of adverse drug effects. In order to implement the mentioned approach, the method for simultaneous determination of carbamazepine and carbamazepine-10,11-epoxide in human serum using HPLC-MS/MS was developed.